2020
DOI: 10.3389/fpsyt.2020.00814
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal Self-Injury: Its Associations With Pathological Internet Use and Psychopathology Among Adolescents

Abstract: Background/Hypotheses: As risk factors for nonsuicidal self-injury (NSSI), most studies highlight the importance of internalising disorders, while only a few researches show the connection between externalising disorders and NSSI. Although some papers have introduced the idea that increasing prevalence rates of NSSI are connected to the broader use of the internet, associations between NSSI and pathological internet use (PIU) are understudied. According to our hypothesis, there is a connection between PIU and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
2
16
0
3
Order By: Relevance
“…Hence, it is vital to explore the relation between IA and NSSI in adolescents. Some empirical studies have posited that IA could increase the likelihood of engaging in NSSI (H.-C. Liu et al, 2017;Mészáros et al, 2020). A recent longitudinal study revealed that IA positively predicted NSSI among adolescents after a 1-year follow-up (Pan & Yeh, 2018).…”
Section: Ia and Nssimentioning
confidence: 99%
“…Hence, it is vital to explore the relation between IA and NSSI in adolescents. Some empirical studies have posited that IA could increase the likelihood of engaging in NSSI (H.-C. Liu et al, 2017;Mészáros et al, 2020). A recent longitudinal study revealed that IA positively predicted NSSI among adolescents after a 1-year follow-up (Pan & Yeh, 2018).…”
Section: Ia and Nssimentioning
confidence: 99%
“…The meta-analysis results showed that alexithymia had a large positive correlation with MPA among Chinese students (r = 0.41). The cognitive-behavioral theory of pathological internet use holds that psychopathological status and maladjustment are important factors affecting MPA ( 80 ). In the process of real interpersonal communication, students with alexithymia often have some problems, such as low sensitivity to understand emotional changes and lack of verbal expression ability, which have a negative impact on their normal interpersonal communication ( 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Internet addiction may allow adolescents to escape from difficult feelings and experiences in their life ( 40 ). One study indicated that problematic internet use alone is not a risk factor for NSSI but might become a risk factor in the presence of comorbid psychiatric disorders ( 41 ). A systematic review focusing on the relationship between problematic internet use, suicidality and NSSI, and it showed that a higher prevalence of NSSI of the subjects with problematic internet use, with point prevalence varying considerably between 1.6 and 18.7% ( 42 ).…”
Section: Discussionmentioning
confidence: 99%